# Class 12 RD Sharma Solutions – Chapter 19 Indefinite Integrals – Exercise 19.9 | Set 1

• Last Updated : 30 Apr, 2021

### Question 1. ∫(log⁡x)/x dx

Solution:

Given that, I = ∫(log⁡x)/x dx

Attention reader! All those who say programming isn't for kids, just haven't met the right mentors yet. Join the  Demo Class for First Step to Coding Coursespecifically designed for students of class 8 to 12.

The students will get to learn more about the world of programming in these free classes which will definitely help them in making a wise career choice in the future.

Let us considered log⁡x = t

Now differentiating both side we get,

d(log⁡x) = dt

1/x dx = dt

dx = xdt

Then, put log⁡x = t and dx = xdt, we get

I = ∫ t/x × (x)dt

= ∫ tdt

= t2/2 + c

= (log⁡x)2/2 + c

Hence, I = (log⁡x)2/2 + c

### Question 2.∫(log⁡(1 + 1/x))/(x(1 + x)) dx

Solution:

Given that I = ∫(log⁡(1 + 1/x))/(x(1 + x)) dx   ……(i)

Let us considered log⁡(1 + 1/x) = t then

On differentiating both side we get,

d[log⁡(1 + 1/x)]=dt

1/(1 + 1/x) × (-1)/x2dx = dt

1/((x + 1)/x) × (-1)/x2dx = dt

(-x)/(x2 (x + 1)) dx = -dt

dx/(x(x + 1)) = -dt

Now, on putting log⁡(1 + 1/x) = t and dx/(x(x + 1)) = -dt in equation (i), we get

I = ∫t × -dt

= -t2/2 + c

= -1/2 [log⁡(1 + 1/x)]2 + c

Hence, I = -1/2 [log⁡(1 + 1/x)]2 + c

### Question 3. ∫((1 + √x )2)/√x dx

Solution:

Given that I = ∫((1 + √x)2)/√x dx

Let us considered (1 + √x) = t then,

On differentiating both side we get,

d(1 + √x) = dt

1/(2√x) dx = dt

dx = dt × 2√x

Now on putting (1 + √x) = t and dx = dt × 2√x, we get

I = ∫t2/√x × dt × 2√x

= 2∫t2dt

= 2 × t3/3 + c

= 2/3[1 + √x]3 + c

Hence, I = 2/3(1 + √x)3 + c

### Question 4. ∫√(1 + ex) ex d

Solution:

Given that I = ∫√(1 + ex) ex dx  ……(i)

Let us considered 1 + ex = t then,

On differentiating both side we get,

d(1 + ex) = dt

ex dx = dt

dx = dt/ex

Now on putting 1 + ex = t and dx = dt/ex in equation (i), we get

I = ∫√t × ex × dt/ex

= ∫ t1/2 dt

= 2/3t3/2 + c

= 2/3 (1 + ex)3/2+c

### Question 5. ∫∛(cos2x) sin⁡x dx

Solution:

Given that I = ∫∛(cos2x) sin⁡x dx    ……(i)

Let us considered cos⁡x = t then,

On differentiating both side we get,

d(cos⁡x) = dt

-sin⁡xdx = dt

dx = -dt/(sin⁡x))

Now on putting cos⁡x = t and dx = -dt/(sin⁡x) in equation (i), we get

I = ∫∛(t2) sin⁡x × (-dt)/(sin⁡x)

= -∫t2/3 sin⁡x dt/(sin⁡x)

= -∫ t2/3 dt

= -3/5 × t5/3

Hence, I = -3/5(cos⁡x)5/3 + c

### Question 6. ∫ex/(1 + ex)2 dx

Solution:

Given that I = ∫ex/(1 + ex)2 dx   …….(i)

Let us considered 1 + ex = t then,

On differentiating both side we get,

d(1 + ex) = dt

ex dx = dt

dx = dt/ex

Now on putting 1 + ex = t and dx = dt/ex in equation (i), we get

I = ∫ex/t2 × dt/ex

= ∫dt/t2

= ∫t-2 dt

= -t-1 + c

= -1/t + c

= -1/(1 + ex) + c

Hence, I = -1/(1 + ex) + c

### Question 7. ∫cot3⁡x cosec2⁡x dx

Solution:

Given that I = ∫cot3⁡x cosec2⁡x dx   …….(i)

Let us considered cot⁡x = t then,

On differentiating both side we get,

d(cotx) = dt

-cosec2x dx = dt

dx = -dt/cosec2x

Now on putting cot⁡x = t and dx = -dt/(cosec2⁡x) in equation (i), we get

I = ∫ t3 cosec2x × (-dt)/(cosec2⁡x)

= -∫ t3 dt

= -t4/4 + c

= -(cot4⁡x)/4 + c

Hence, I = -(cot4⁡x)/4 + c

### Question 8. Solution:

Given that I = [Tex] [/Tex] …….(i)

Let us considered sin-1⁡x = t then,

On differentiating both side we get,

d(sin-1x) = dt

1/√(1 – x2)dx = dt

dx = √(1 – x2) dt)

Now on putting sin-1x = t and dx = √(1 – x2) dt in equation (i), we get

I = ∫ (et)2/√(1 – x2) × √(1 – x2) dt

= ∫e2t dt

= e2t/2 + c + c

Hence, I = + c

### Question 9. ∫(1 + sin⁡x)/√(x – cos⁡x) dx

Solution:

Given that I = ∫(1 + sin⁡x)/√(x – cos⁡x) dx    ……..(i)

Let us considered x – cos⁡x = t, then

On differentiating both side we get,

d(x – cos⁡x) = dt

[1 – (-sin⁡x)]dx = dt

(1 + sin⁡x)dx = dt

Now on putting x – cos⁡x = t and (1 + sin⁡x)dx = dt in equation (i), we get

I = ∫ dt/√t

= ∫ t-1/2 dt

= 2t1/2 + c

= 2(x – cos⁡x)1/2 + c

Hence, I = 2√(x – cos⁡x) + c

### Question 10.  ∫1/(√(1 – x2) (sin-1x)2) dx

Solution:

Given that I = ∫1/(√(1 – x2) (sin-1⁡x)2) dx   …..(i)

Let us considered sin-1⁡x = t then,

On differentiating both side we get,

d(sin-1⁡x) = dt

1/√(1 – x2 ) dx = dt

Now on putting sin-1⁡x = t and 1/√(1 – x2) dx = dt in equation (i), we get

I = ∫dt/t2

= ∫t-2 dt

= -t-1 + c

= (-1)/t + c

= (-1)/(sin-1⁡x) + c

Hence, I = (-1)/(sin-1⁡x) + c

### Question 11. ∫(cot⁡x)/√(sin⁡x) dx

Solution:

Given that I = ∫(cot⁡x)/√(sin⁡x) dx    …….(i)

Let us considered sin⁡x = t then,

On differentiating both side we get,

d(sin⁡x) = dt

cos⁡xdx = dt

Now, I = ∫(cot⁡x)/√(sin⁡x) dx

= ∫(cos⁡x)/(sin⁡x√(sin⁡x)) dx

= ∫ cos⁡x/(sin⁡x)3/2dx

= ∫ cos⁡x/(sin⁡x)3/2 dx   …….(ii)

Now on putting sin⁡x = t and cos⁡xdx = dt in equation (ii), we get

I = ∫ dt/t3/2

= ∫ t-3/2 dt

= -2t-1/2 + c

= -2/√t + c

= -2/√(sin⁡x) + c

I = -2/√sin⁡x + c

### Question 12. ∫(tan⁡x)/√(cos⁡x) dx

Solution:

Given that I = ∫(tan⁡x)/√(cos⁡x) dx

I = ∫sin⁡x/cos⁡x√(cos⁡x) dx

= ∫ sin⁡x/(cos⁡x)3/2 dx

= ∫sin⁡x/(cos⁡x)3/2 dx   ……..(i)

Let us considered cos⁡x = t then,

On differentiating both side we get,

d(cos⁡x) = dt

-sin⁡xdx = dt

sin⁡xdx = -dt

Now on putting cos⁡x = t and sin⁡xdx = -dt in equation (i), we get

I = ∫(-dt)/t-3/2

= -∫t-3/2 dt

= -[-2t-1/2] + c

= 2/t1/2 + c

= 2/√(cos⁡x) + c)

Hence, I = 2/√(cos⁡x) + c

### Question 13. ∫cos3x/√(sin⁡x) dx

Solution:

Given that I = ∫cos3⁡x/√(sin⁡x) dx

= ∫(cos2xcos⁡x)/√(sin⁡x) dx

= ∫((1 – sin2⁡x)cos⁡x)/√(sin⁡x) dx

= ∫((1 – sin2x))/√(sin⁡x) cos⁡xdx ……(i)

Let us considered  sin⁡x = t then,

On differentiating both side we get,

d(sin⁡x) = dt

cos⁡xdx = dt

Now on putting sin⁡x = t and cos⁡xdx = dt in equation (i), we get

I = ∫(1 – t2)/√t dt

= ∫(t-1/2-t2 x t-1/2)dt

=∫(t-1/2 – t3/2)dt

= 2t1/2 – 2/5 t5/2 + c

= 2(sin⁡x)1/2 – 2/5(sin⁡x)5/2 + c

Hence, I = 2√(sin⁡x) – 2/5(sin⁡x)5/2 + c

### Question 14. ∫(sin3x)/√(cos⁡x) dx

Solution:

Given that I = ∫(sin3⁡x)/√(cos⁡x) dx

= ∫(sin2⁡xsin⁡x)/√(cos⁡x) dx

=∫((1 – cos2⁡x))/√(cos⁡x) sin⁡xdx …….(i)

Let us considered cos⁡x = t then,

On differentiating both side we get,

d(cos⁡x) = dt

-sin⁡xdx = dt

sin⁡xdx = -dt

Now on putting cos⁡x = t and sin⁡xdx = -dt in equation (i), we get

I = ∫((1 – t2))/√t × -dt

= ∫(t2 – 1)/√t dt

= ∫(t2/t1/2 – 1/t1/2)dx

= ∫(t2-1/2 – t-1/2)dt

= ∫(t3/2 – t1/2)dt

= 2/5 t5/2 – 2t1/2 + c

= 2/5 cos5/2⁡x – 2cos1/2⁡x + c

Hence, I = 2/5 cos5/2x – 2√(cos⁡x) + c

### Question 15. ∫1/(√(tan-1x) (1 + x2)) dx

Solution:

Given that I = ∫1/(√(tan-1x) (1 + x2)) dx  …..(i)

Let us considered tan-1⁡x = t, then

On differentiating both side we get,

d(tan-1⁡x) = dt

1/(1 + x2) dx = dt

Now on putting tan-1⁡x = t and 1/(1 + x2) dx = dt in equation (i), we get

I = ∫1/√t dt

= ∫t-1/2 dt

= 2t1/2 + c

= 2√tan-1⁡x + c

Hence, I = 2√tan-1⁡x + c

### Question 16. ∫√(tan⁡x)/(sin⁡xcos⁡x) dx

Solution:

Given that I = ∫√(tan⁡x)/(sin⁡xcos⁡x) dx

= ∫(√(tan⁡x)×cos⁡x)/(sin⁡xcos⁡x×cos⁡x) dx

= ∫√(tan⁡x)/(tan⁡xcos2⁡x) dx

= ∫(sec2⁡xdx)/√(tan⁡x) dx

Let us considered tan⁡x = t, then

On differentiating both side we get,

sec2⁡xdx = dt

Now

I = ∫ dt/√t

= 2√t + c

Hence, I = 2√tan⁡x + c

### Question 17. 1/x × (log⁡x)2 dx

Solution:

Given that I = ∫1/x × (log⁡x)2 dx   …..(i)

Let us considered log⁡x = t then,

On differentiating both side we get,

d(log⁡x) = dt

1/x dx = dt

Now on putting log⁡x = t and 1/x dx = dt in equation (i), we get

I = ∫t2 dt

= t3/3 + c

= (log⁡x)3/3 + c

Hence, I = (log⁡x)3/3 + c

### Question 18. ∫sin5x cos⁡x dx

Solution:

Given that I = ∫sin5⁡x cos⁡x dx  ……(i)

Let us considered sin⁡x = t then,

On differentiating both side we get,

d(sin⁡x) = dt

cos⁡xdx = dt

Now on putting sin⁡x = t and cos⁡xdx = dt in equation (i), we get

I = ∫ t5 dt

= t6/6 + c

= (sin6⁡x)/6 + c

Hencec, I = 1/6 (sin6⁡x) + c

### Question 19. ∫tan3/2⁡x sec2⁡x dx

Solution:

Given that I = ∫tan3/2⁡xsec2⁡xdx  ……(i)

Let us considered tan⁡x = t then,

On differentiating both side we get,

d(tan⁡x) = dt

sec2⁡xdx = dt

Now on putting tan⁡x = t and sec2xdx = dt in equation (i), we get

I = ∫ t3/2 dt

= 2/5 t5/2 + c

= 2/5(tan⁡x)5/2 + c

Hence, I = 2/5 tan5/2⁡x + c

### Question 20. ∫(x3)/(x2 + 1)2dx

Solution:

Given that I = ∫(x3)/(x2 + 1)2dx …….(i)

Let us considered 1 + x2 = t then,

On differentiating both side we get,

d(1 + x2) = dt

2xdx = dt

xdx = dt/2

Now on putting 1 + x2 = t and xdx = dt/2 in equation (i),we get

I = ∫x2/t3 × dt/2

= 1/2∫(t – 1)/t3 dt         [1 + x2 = t]

= 1/2∫[(t/t3 – 1/t3)dt]

= 1/2∫(t-2 – t-3)dt

= 1/2 [-1t-1 – t-2/(-2)] + c

= 1/2 [-1/t + 1/(2t2)] + c

= -1/2t + 1/(4t2) + c

= -1/2(1 + x2) + 1/(4(1 + x2)2) + c

= (-2(1 + x2) + 1)/(4(1 + x2)2) + c

= (-2 – 2x2 + 1)/(4(1 + x2)2) + c

= (-2x2 – 1)/(4(1 + x2)2) + c

= -(1 + 2x2 )/(4(x2 + 1)2) + c

Henec, I = -(1 + 2x2)/(4(x2 + 1)2) + c

### Question 21. ∫(4x + 2)√(x2 + x + 1) dx

Solution:

Given that I = ∫(4x + 2)√(x2 + x + 1) dx

Let us considered x2 + x + 1 = t then,

On differentiating both side we get,

(2x + 1)dx = dt

Now,

I = ∫ (4x + 2)√(x2 + x + 1) dx

= ∫2√t dt

= 2∫√t dt

= 2t3/2/(3/2) + c

Hence, I = 4/3 (x2 + x + 1)3/2 + c

### Question 22. ∫(4x + 3)/√(2x2 + 3x + 1) dx

Solution:

Given that l = ∫(4x + 3)/√(2x2 + 3x + 1) dx  ……(i)

Let us considered 2x2 + 3x + 1 = t then,

On differentiating both side we get,

d(2x2 + 3x + 1) = dt

(4x + 3)dx = dt

Now on putting 2x2 + 3x + 1 = t and (4x + 3)dx = dt in equation (i), we get

I = ∫dt/√t

= ∫t-1/2 dt

= 2t1/2 + c

= 2√t + c

Hence, I = 2√(2x2 + 3x + 1) + c

### Question 23. ∫1/(1 + √x) dx

Solution:

Given that I = ∫1/(1 + √x) dx   …….(i)

Let us considered x = t2 then,

On differentiating both side we get,

dx = d(t2)

dx = 2tdt

Now on putting x = t2 and dx = 2tdt in equation (i), we get

I = ∫2t/(1 + √(t2)) dt

= ∫2t/(1 + t) dt

= 2∫t/(1 + t) dt

= 2∫(1 + t – 1)/(1 + t) dt

= 2⌋[(1 + t)/(1 + t) – 1/(1 + t)]dt

= 2∫dt – 2∫1/(1 + t) dt

= 2t – 2log⁡|(1 + t)| + c

= 2√x – 2log⁡|(1 + √x)| + c

Hence, I = 2√x – 2log⁡|(1 + √x)| + c

### Question 24. Solution:

Given that I = …….(i)

Let us considered cos2x = t then,

On differentiating both side we get,

d(cos2⁡x) = dt

-2cos⁡x sin⁡x dx = dt

-sin⁡2x dx = dt

sin⁡2x dx = -dt

Now on putting cos2⁡x = t and sin⁡2x dx = -dt in equation (i), we get

I = ∫et(-dt)

= -et + c

= – + c

Hence, I = – + c

My Personal Notes arrow_drop_up